Plan drawing of Twin Cities streetcar snowplow (Minnesota Streetcar Museum)
5b0a3e85c7bb83f9d447112d42f28cb1
United States
Minnesota
5b0a3e85c7bb83f9d447112d42f28cb1
Right side view and interior view of streetcar snowplow built by Twin City Rapid Transit.
contact MSM for permission to use
Keywords: streetcars; Twin City Rapid Transit Co.; Transportation